Spectroscopic properties of heavy metal oxide glasses doped with Er3+ ions for mid-infrared applications - Ragin, Tomasz; Zmojda, Jacek Mariusz; Kochanowicz, Marcin; Dorosz, Dominik (Photonics Letters of Poland, 2015)
In this paper, bismuth-germanate glasses doped with erbium ions have been synthesized. The composition of glass has been selected in terms of good thermal stability, high transparency in the near infrared region and high refractive index. The luminescence at a wavelength of 1534nm has been obtained as a result of radiative transition 4I13/2 → 4I15/2 in erbium ions due to 98 nm laser diode excitation. Different emission intensity in produced glasses has been observed as a result of various molar concentration of erbium in the glass matrix. The highest luminescence value has been obtained in glass doped with 1.0 mol% Er2O3. Full Text: PDF References Y. Gangfeng, L. Tao, "Broadband 1.53 μm emission in Er3+-doped Ga-Bi-Pb-Ge heavy metal oxide glasses", J. Rare Earths 26, 924 (2008). CrossRef Y. Guo, Y. Tian, L. Zhang, L. Hu, J. Zhang, "Erbium doped heavy metal oxide glasses for mid-infrared laser materials", J. Non-Cryst. Solids 377, 119 (2013). CrossRef K. Biswas, A.D. Sontakke, R. Sen, K.Annapurna, "Enhanced 2 μm broad-band emission and NIR to visible frequency up-conversion from Ho3+/Yb3+ co-doped Bi2O3–GeO2–ZnO glasses", Spec. Acta P. A: Molec. Biomolec. Spect. 112, 301 (2013). CrossRef D.M. Shi, Y.G. Zhao, Q. Qian, D.D. Chen, Q.Y. Zhang, "Role of PbO substitution by Bi2O3 on 1.47 μm luminescence properties of Tm3+/Tb3+-doped Bi2O3–GeO2–Ga2O3 glass", J. Alloys Comp. 499, 126 (2010). CrossRef D. Dorosz, J. Żmojda, M. Kochanowicz, W. Mazerski, "Upconversion luminescence in tellurite glass codoped with Yb3+/Ho3+ ions", Proc. SPIE 8903, 890307-1 (2013). CrossRef D. Dorosz, Special active optical fibers (Papers of the commision on ceramic science Polish Ceramic Bulletin, Polish Ceramic Society Kraków-Białystok 2010). Z. Jihong, T. Haizheng, Z. Xiujian, "Upconversion luminescence properties of Er3+ doped GeS2 -Ga2 S3 -KCl chalcohalide glasses", Rare Metals 30, 18 (2011). CrossRef Q. Chen, H. Wang, Q. Wang, Q. Chen, "Structural study of the origin of the largest 1.5 μm Er3+ luminescence band width in multicomponent silicate glass", J. Non-Cryst. Solids 404, 145 (2014). CrossRef A. Langar, C. Bouzidi, H. Elhouichet, M. Ferid, "Er–Yb codoped phosphate glasses with improved gain characteristics for an efficient 1.55 µm broadband optical amplifiers", J. Luminescence 148, 249 (2014). CrossRef V.A.G. Rivera, L.C. Barbosa, "Spectroscopic properties of Er3+-doped sodium-modified tellurite glasses for use as optical amplifiers at 1540 nm", J. Luminescence 156, 116 (2014). CrossRef T. Wei, F. Chen, Y. Tian, S. Xu, "Broadband near-infrared emission property in Er3+/Ce3+ co-doped silica–germanate glass for fiber amplifier", Spect. Acta P. A: Mol. Bio. Spect. 126, 53 (2014). CrossRef